Measuring perception and the level of satisfaction towards event management provided by the Magellan Sutera Resort / Charlotte Charles - Charles, Charlotte (2012)
This report measures the perception and level of satisfaction towards event management provided by The Magellan Sutera Resort and what factors that may influence the service quality of event management and how does it affect the level of satisfaction for attendee. Events and meeting has become a prominent contribution in tourism industry (Presburg and Edwards,2005). In effort to maintain the service quality of event, attendees who have attended the events can be a reliable source of information in measuring the succession of events. Therefore, every department who may directly or indirectly involved can benefit from the outcome of this research especially in enhancing their efficacy in managing the event. A total of 120 respondents from four different organizers were randomly selected. The researcher distributed questionnaire to the attendee which they filled out and also gave their views, opinions and recommendations on how to enhance the service quality of event management. Using qualitative analysis, the data obtained were analyzed using Microsoft Excel and converted into pie charts, bar charts and percentage. From the information obtained, the main finding is that the quality of service, quality of food, venue and also value of money can influence the attendees' level of satisfaction. The researcher hopes that this study can give provide The Magellan Sutera Resort an insight regarding the areas to improve, with respect to the departments that involved the preparation of event.